Comparative Effects of Isometric and Isotonic Progressive Continuous Exercise on miRNA-155 Expression Following Sports-Related Muscle Injury - Moh. Ali Imron; Suci Muqodimatul; I Made Jawi; I Putu Gede Adiatmika; Pamudji Utomo (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2026)
Background: Background: Muscle injury often causes pain, inflammation, and reduced function. MicroRNA-155 (miRNA-155) is involved in inflammatory regulation and tissue regeneration after skeletal muscle injury. Exercise rehabilitation may influence these molecular responses, but evidence regarding different exercise modalities remains limited. Objective: To compare the effects of isometric progressive continuous exercise (MPCE) and isotonic progressive continuous exercise (NPCE) on miRNA-155 expression in athletes with grade 1–2 muscle injury. Method: A true experimental randomized pretest–posttest control group design was used. Twenty-one athletes with grade 1–2 muscle injury were randomly assigned to MPCE (n = 7), NPCE (n = 7), or control (CON; n = 7). Intervention groups performed progressive continuous exercise once daily for 7 consecutive days, while the control group received no exercise intervention. Venous blood samples were collected before and after intervention, and miRNA-155 expression was analyzed using real-time quantitative polymerase chain reaction (qPCR). Data were analyzed using within-group tests, Kruskal–Wallis, and post-hoc analysis.. Result: In the MPCE group, miRNA-155 increased from 0.583 ± 0.5 to 3.700 ± 3.6, but the change was not significant (p = 0.066). In the NPCE group, miRNA-155 significantly decreased from 14.273 ± 1.3 to 5.645 ± 3.6 (p = 0.001). The control group showed no significant change from 1.119 ± 1.6 to 1.598 ± 1.4 (p = 0.310). Between-group analysis showed significant differences in baseline values (H = 13.406, p = 0.001) and change scores (H = 12.276, p = 0.002). Post-hoc analysis revealed significant differences between both intervention groups and control, while no difference was found between MPCE and NPCE. Conclusion: Progressive continuous exercise significantly modulated miRNA-155 expression compared with the control group. However, no significant difference was found between MPCE and NPCE, and results should be interpreted with caution due to baseline imbalance. Further studies with larger samples and adjusted analyses are warranted.